2022
DOI: 10.1177/11786329211067325
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy of Newly-Admitted Cancer Patients in Vietnam: Difficulties Understanding Treatment Options and Processing Health-Related Information

Abstract: Having a good understanding of cancer patients’ health literacy in the early stage of diagnosis can help to implement strategies to improve the management process and overall health outcomes. The study aims to describe health literacy and its association with socio-demographic characteristics among newly admitted cancer patients. A cross-sectional study was conducted on 262 newly admitted patients of a cancer hospital in Vietnam using the Vietnamese version of the HLS-SF12 questionnaire. Descriptive analytics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 72 publications
0
7
0
3
Order By: Relevance
“… 44 , 45 The included patients could independently answer the questionnaire, suggesting that their health status could be similar between the advanced and early stages. Besides, cancer patients in Vietnam might have low health literacy and perceive cancer as a catastrophic disease regardless of the stages; 46 therefore, they might be concerned about cancer of all stages similarly. The finding about gender was in line with the previous studies explaining that female cancer patients tended to have worse HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“… 44 , 45 The included patients could independently answer the questionnaire, suggesting that their health status could be similar between the advanced and early stages. Besides, cancer patients in Vietnam might have low health literacy and perceive cancer as a catastrophic disease regardless of the stages; 46 therefore, they might be concerned about cancer of all stages similarly. The finding about gender was in line with the previous studies explaining that female cancer patients tended to have worse HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…37 The most common determinants associated with their HL level were age, 13,15,16,24,36,15,40,41,44,45,53 -70 education, 13,16,24,30,32,15,35 -37,39,40,44,45,50,52 -58,60 -66,68,71 …”
Section: Resultsmentioning
confidence: 99%
“…Based on the characteristics of the population in these studies, the percentages of inadequate, low, or limited HL levels varied between 3.5% (among 4589 cancer patients in China) 24 and 84.5% (among 1360 community residents aged 15-69 years in Shanghai). 37 The most common determinants associated with their HL level were age, 13,15,16,24,36,15,40,41,44,45,53 -70 education, 13,16,24,30,32,15,35 -37,39,40,44,45,50,52 -58,60 -66,68,71 …”
Section: Resultsmentioning
confidence: 99%
“…In other words, inadequate literacy among the elderly reduces their quality of life. Another study showed that older age, lower level of education, and living in rural areas are associated with lower health literacy (36). The results can be explained from another angle.…”
Section: Discussionmentioning
confidence: 97%
“…Age hurts 3 dimensions of health literacy: Health care system, health promotion, and disease prevention. As a result, it can be found that older patients have more difficulty finding information about mental health management (36). Poor health literacy can lead to cancer patients' behavior: Poor health, limited access to health care, reduced understanding of medical information, lack of interaction with physicians and health care personnel, and inconsistencies with treatment plans (37).…”
Section: Introductionmentioning
confidence: 99%